Atrial ectopes and atrial fibrillation association - Melo Neto, Jônatas; Pereira Valdigem, Bruno (JOURNAL OF CARDIAC ARRHYTHMIAS, 2017)
Atrial electrical instability is a recently incorporated term in medical practice to describe the broad spectrum of overlapping atrial arrhythmias. This relationship was already intuitive between atrial flutter and atrial fibrillation (which gave birth to the so-called “fibril-flutter”), and has more recently been related to atrial tachycardias and atrial fibrillation. This relationship is extremely important, since the diagnosis of atrial fibrillation implies in strategies to prevent embolic events. With new screening methods, the diagnosis of atrial fibrillation has become more frequent (prolonged monitoring, implantable monitors, pacemaker telemetry). The presence of atrial extrasystoles and atrial tachycardia is a challenge: despite the intuitive relationship of higher risk for atrial fibrillation and cerebrovascular events, the scientific evidence became more robust recently. This article intends to aggregate the best quality evidence available to facilitate the choice of an appropriate strategy for a patient with tachycardia and atrial extrasystoles and to adequately assess their risk.